SAT0362 Mycophenolate Mofetil versus Methotrexate in The Management of Large Vessel Giant Cell Arteritis. (15th July 2016) - Dospinescu, P.I.; Karabayas, M.; Kidder, D.; Fluck, N.; Erwig, L.; Mason, J.; Basu, N.
Abstract : Background: There is an unmet clinical need to identify an effective conventional adjuvant immunosuppressive agent in the treatment of large vessel giant cell arteritis. Traditionally the therapeutic approach has employed prolonged courses of high dose glucocorticosteroids (GC) with poor long-term outcomes. Methotrexate (MTX) is currently recommended as adjuvant GC sparing immunosuppression based on modest evidence 1, 2 . Evidence for the use of Mycophenolate mofetil (MMF) in this setting is lacking. Objectives: We investigated the outcome of MMF and MTX usage in an extended cohort of large vessel giant cell arteritis (LVV-GCA) patients from 2 large tertiary centres in the United Kingdom. Methods: We retrospectively analysed laboratory and treatment outcomes for United Kingdom patients diagnosed with LVV-GCA between January 2008 and January 2015 who attended two geographically distinct specialist Vasculitis Clinics. The two centres use different first line GC sparing agents in LVV GCA, one generally uses MMF the other MTX. Following retrospective record review, cases were selected based on radiologic evidence of large vessel vasculitis, fulfilment of the Chapel Hill Consensus Conference 2012 GCA definition and a first line prescription of GC with adjuvant MMF or MTX. Baseline and follow up characteristics were collated. Unpaired t-test was used to compare differences between the groups. Results: Twenty patients (7 male) were identified in total: 11 patients (3 male) treated with MMF and 9 patients (4 male) treated with MTX. Mean age (SD) at diagnosis was 66.15 (7.1) years with the MMF group being older (68.9 (5.9) versus 62.7 (7.2) years). Positron emission tomography–computed tomography (PET CT) confirmed evidence of active large vessel vasculitis in all patients. At diagnosis, there was no significant difference between the mean CRP value between the two groups (56.1 (46.9) versus 47.7 (34.3) mg/l, p=0.67). Following 6 weeks of treatment, there was a dramatic reduction in the mean CRP level in both groups (8.1 (8.7) versus 3.1 (2.2), p=0.14), a response which was maintained at one year (7.6 (5.8) versus 4.5 (3.1), p=0.16). Although at diagnosis Prednisolone dose was higher in the MMF group (54.5 (9.3) versus 41.1 (17.6) mg, p=0.042), no significant difference was found between the groups at 6 weeks (24.1 (5.4) versus 29.1 (12.8) mg, p=0.26) and throughout the year (8.4 (2.8) versus 5.8 (3.7) mg, p=0.1 at one year) Conclusions: To our knowledge, we describe the first case-series of MMF use in LV-GCA. Within the limitations of this study, MMF appears to be comparable to MTX as adjunctive therapy in patients with LV-GCA, allowing a rapid taper of GC. A randomized controlled trial is required to further evaluate the role of MMF in this challenging disease subset. References: Mukhtyar C et al. EULAR recommendations for the management of large vessel vasculitis. Ann Rheum Dis. 2009 Mar; 68(3):318–23. Mahr AD et al. Adjunctive Methotrexate for treatment of giant cell arteritis: an individual patient data meta-analysis. Arthritis Rheum 2007; 56:2789–97. Disclosure of Interest: None declared